Narrative listening to the narrative listeners - Mitchell, Katherine Jane, author; Wolfgang, David, advisor; Jacobsen, Jaime, committee member; Knobloch, Katie, committee member (Colorado State University. Libraries, 2025)
When we engage in narrative listening, the purposeful act of attending to another's story, we are ideally a part of an agreement that a co-construction of a person's understanding of their own narrative identity is underway (Bamberg & Georgakopoulou, 2008; McAdams, 2013). However, the act of narrative listening, as it is practiced in the world, is not simply to understand someone's story. From the doctor's office to a car share with a stranger, the possible aims might be to better serve, heal, align, and even debate, the teller. My research pursues how vocational listeners have infused this skill into their lives, why, and by what effect. In developing an understanding of narrative listening, I was part of a team that created a podcast series wherein the interviewer conducts a session with a person whose vocation depends on their narrative listening skills (healers, leaders, servers, etc.). For this thesis, I collected data from the seasons we recorded and conducted a reflexive textual analysis of the interview transcripts. This analysis focused on uncovering the patterns and nuances in how narrative listeners engage with stories across two vocations: healers and leaders. Key aspects of the analysis included identifying the different intentions behind listening—such as empathy, curiosity, and goal-oriented listening. By examining the methods and effects of narrative listening, this research enhances our understanding of how stories are received and co-constructed. Ultimately, the findings from this study support the grounded development of narrative listening theory, a framework that can be applied to improve communication practices across a wide range of fields.
Keywords: narrative identity; listening; podcast